2018
DOI: 10.1371/journal.pone.0208364
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic multidrug-resistant microorganisms among small companion animals in Germany

Abstract: Antimicrobial multidrug-resistant microorganisms (MDRO) can be transmitted between companion animals and their human owners. Aim of this study was to determine the prevalence of extended spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-E) and Staphylococcus aureus including methicillin-resistant S. aureus (MRSA) in different companion animal species. Dogs (n = 192), cats (n = 74), and rabbits (n = 17), treated in a veterinary practice and hospital or living in an animal shelter and private households… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 77 publications
1
43
1
4
Order By: Relevance
“…The conclusion of the authors that Staphylococcus was found to be an indicator OTU for MRSA-negative pigs cannot be confirmed by our results because we have found staphylococci in all individuals and almost all samples (52/54) [31]. Considering that coagulase-negative staphylococci (CoNS) from human and animal sources may harbor mec genes as part of mobile SCCmec elements and therefore may act as a reservoir for methicillin resistance, experimental approaches to conquer LA-MRSA in pigs by competitive colonization with CoNS are questionable [9,[33][34][35].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The conclusion of the authors that Staphylococcus was found to be an indicator OTU for MRSA-negative pigs cannot be confirmed by our results because we have found staphylococci in all individuals and almost all samples (52/54) [31]. Considering that coagulase-negative staphylococci (CoNS) from human and animal sources may harbor mec genes as part of mobile SCCmec elements and therefore may act as a reservoir for methicillin resistance, experimental approaches to conquer LA-MRSA in pigs by competitive colonization with CoNS are questionable [9,[33][34][35].…”
Section: Discussionmentioning
confidence: 58%
“…This subgroup of MRSA can colonize both humans and pigs, and occurrence of the predominant clonal complex (CC) 398 is particularly high in regions with intensive pig farming [6][7][8]. Moreover, LA-MRSA also colonizes healthy companion animals and horses without contact to livestock, which indicates that a spread to other animals has commenced [9][10][11]. Of note, zoonotic exchange of LA-MRSA between humans and animals has significant impact on the epidemiology of MRSA and contributes to the overall burden of MRSA colonization and infection in Germany and other countries [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…All LA-MRSA in our study could be assigned to CC398 and spa -types t011 and t034, which are the major LA-MRSA-associated spa -types recovered from farm animals, companion animals, and humans in Germany and Europe in general [ 33 , 34 , 35 ]. Interestingly, two other research groups isolated LA-MRSA of the same clonal complex and spa -types from CF airways, which also did not carry the bacteriophage-associated genes sak , chps , and scin either [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…, Kaspar et al . ), it is the responsibility of all prescribers of antibiotics to use these medications in a rational manner. Unrestrained antibiotic use in small animals can, and will, contribute to the development of antibiotic resistance in bacteria that pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic use is recognised as a key driver of AMR (Klein et al 2018). Given that the transfer of multi-resistant bacteria from companion animals to people has been demonstrated (Guardabassi et al 2004, Harrison et al 2014, Zhang et al 2016, Kaspar et al 2018, it is the responsibility of all prescribers of antibiotics to use these medications in a rational manner. Unrestrained antibiotic use in small animals can, and will, contribute to the development of antibiotic resistance in bacteria that pose a threat to human health.…”
Section: Introductionmentioning
confidence: 99%